2020
DOI: 10.3389/fmolb.2020.00035
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Increased Expression of Yin Yang 2 to Development of Cardiomyopathy

Abstract: Yin Yang 2 (YY2) is a member of the Yin Yang family of transcription factors. Although the bioactivity of YY2 has been previously studied, its role in cardiovascular diseases is not known. We observed the increased expression of YY2 in failing human hearts compared with control hearts, raising the question of whether YY2 is involved in the pathogenesis of cardiomyopathy. To investigate the potential contribution of YY2 to the development of cardiomyopathy, we crossed two independent transgenic (Tg) mouse lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…Similar to the YY1 protein, as shown by Drews et al , the expression of YY2 might be ubiquitous as well since YY2 mRNA could be detected in the entire embryonic mice 19 . Indeed, YY2 is expressed in various types of tissues, including the cardiovascular, neuronal, breasts, muscle, eye, stomach, lung, brain and testis 1,7,9,19,20 …”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Similar to the YY1 protein, as shown by Drews et al , the expression of YY2 might be ubiquitous as well since YY2 mRNA could be detected in the entire embryonic mice 19 . Indeed, YY2 is expressed in various types of tissues, including the cardiovascular, neuronal, breasts, muscle, eye, stomach, lung, brain and testis 1,7,9,19,20 …”
Section: Introductionmentioning
confidence: 74%
“…Recently Wu et al showed that YY2 suppresses the expression of MYPN , 23 which expression is needed for normal development of cardiac muscle and its abnormality is associated with cardiomyopathy 36 . On the other hand, Zhang et al reported that elevated levels of YY2 lead to partial embryonic death, while the surviving embryos have impaired proliferation of cardiomyocytes and develop cardiomyopathy 20 . These evidences suggest the importance of stringent YY2 regulation in the differentiation and development of the cardiovascular system.…”
Section: Introductionmentioning
confidence: 99%
“…The following pair of complementary oligos harboring 20-nucleotide guide RNA sequences was used to generate guide RNA (gRNA): forward 5′CAC​CGATC​GCA​CCT​AAG​ATT​AAG​GC3′ and reverse 5′AAA​CGCC​TTA​ATC​TTA​GGT​GCG​ATC3’. The guide oligo was subcloned into pX458 as previously described ( Zhang et al, 2020 ). Briefly, these two complementary oligos (100 μM) were phosphorylated by T4 polynucleotide kinase, annealed by boiling for 10 min, and left at room temperature overnight.…”
Section: Methodsmentioning
confidence: 99%
“…The following pair of complementary oligos harboring 20-nucleotide guide RNA sequences was used to generate guide RNA (gRNA): forward 5′CACCGATCGCA CCTAAGATTAAGGC3′ and reverse 5′AAACGCCTTAATC TTAGGTGCGATC3'. The guide oligo was subcloned into pX458 as previously described (Zhang et al, 2020)…”
Section: Generation Of Homozygous Pgam2-k176r Knock-in C2c12 and P19 ...mentioning
confidence: 99%
“…(1) Te target genes of hub miRNAs were validated for a new dataset (GSE60993) containing gene expression from unstable angina and healthy controls, using AUC and AUPR as evaluation metrics. (2) Transcription factors (TFs) are important proteins that regulate gene expression [56], and their dysregulation will cause abnormal gene expression, which is closely associated with the development and progression of complex diseases [57]. Te TF-Marker database [58] provides cell-and tissue-specifc TFs and related markers.…”
Section: Validation Of the Potential Of Target Genes Asmentioning
confidence: 99%